Pengaruh Kompensasi Terhadap Kinerja Karyawan di CV. XYZ - Siregar, Aida Fitri; Elviana, Elviana; Radi, Andi Muh; Fahmi, Ahmad; Ferianto, Ferianto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze the effect of compensation on employee performance at CV. XYZ, a food supply company in Tangerang. The research applied a quantitative method with 24 employees as respondents. Data were collected using questionnaires tested for validity (r-count > r-table 0.444) and reliability (Cronbach’s Alpha > 0.70). Data analysis was conducted using simple linear regression with SPSS version 26. The classical assumption test showed that the data were normally distributed and free from heteroscedasticity. The regression equation obtained was Y=10.542+0.552XY = 10.542 + 0.552XY=10.542+0.552X, indicating that an increase in compensation improves employee performance. The hypothesis test showed a t-value of 3.409 > t-table 2.074 with a significance level of 0.002 < 0.05, proving that compensation has a positive and significant effect on performance. The coefficient of determination (R²) was 0.371, meaning 37.1% of performance variation is explained by compensation, while 62.9% is influenced by other factors.